Optimisation of Damping in Short Fiber Reinforced Aligned Composites: A Review of literature using Micromechanical Analysis (International Journal of Engineering and Computer Science, 2017)
Vibration damping is becoming increasingly important for improved vibration and noise control, dynamic stability, and fatigue & impact resistance in advanced engineering systems. Specially, there is a strong need for information on methods for improvement of damping in lightweight structural composite materials so that they may be more effectively used in the design of high performance structures and machines. Polymer composites are good candidates in the development of damped structural materials because of their low specific weight and excellent stiffness & damping characteristics. A review is presented on fiber composite materials optimising damping properties and aspect ratios along with experimentally attainable at the micromechanical level.